2017
DOI: 10.1177/0305735617691592
|View full text |Cite
|
Sign up to set email alerts
|

Music Performance Anxiety in adolescence and early adulthood: Its relation with the age of onset in musical training

Abstract: Music Performance Anxiety (MPA) is one of the major emotional problems affecting music professionals and music students; it can only be addressed on a professional basis if a more profound knowledge of determining factors is acquired. This study examines one of these factors, scarcely investigated until now: the age at which an individual began music training. The relation of age of onset with MPA is examined here in two separate samples of music students/pupils in Spain: one of 437 advanced music students (me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
23
0
2

Year Published

2019
2019
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 46 publications
0
23
0
2
Order By: Relevance
“…Kenny writes that this anxiety is manifested through combinations of symptoms that may be affective, cognitive (such as fear of failure or negative thoughts about the performance or about oneself), somatic (such as tremors in the extremities or the voice) or behavioral (such as avoidance or flight behaviors). Anxiety affects adult musicians and children and adolescents alike (Boucher & Ryan, 2011;Zarza-Alzugaray, Orejudo, Casanova, & Aparicio-Moreno, 2018). Between 40 and 60 percent of professional musicians have seen their performance harmed by anxiety (Thomas & Nettelbeck, 2014;Zarza-Alzugaray et al, 2018).…”
Section: Musical Performance Anxietymentioning
confidence: 99%
See 1 more Smart Citation
“…Kenny writes that this anxiety is manifested through combinations of symptoms that may be affective, cognitive (such as fear of failure or negative thoughts about the performance or about oneself), somatic (such as tremors in the extremities or the voice) or behavioral (such as avoidance or flight behaviors). Anxiety affects adult musicians and children and adolescents alike (Boucher & Ryan, 2011;Zarza-Alzugaray, Orejudo, Casanova, & Aparicio-Moreno, 2018). Between 40 and 60 percent of professional musicians have seen their performance harmed by anxiety (Thomas & Nettelbeck, 2014;Zarza-Alzugaray et al, 2018).…”
Section: Musical Performance Anxietymentioning
confidence: 99%
“…Anxiety affects adult musicians and children and adolescents alike (Boucher & Ryan, 2011;Zarza-Alzugaray, Orejudo, Casanova, & Aparicio-Moreno, 2018). Between 40 and 60 percent of professional musicians have seen their performance harmed by anxiety (Thomas & Nettelbeck, 2014;Zarza-Alzugaray et al, 2018). Beyond these effects on performance, there can be other negative consequences, as musicians tend to adopt coping strategies that are not very healthy, including the consumption of drugs and alcohol, sometimes causing not only poorer performance (Williamon, Aufegger, Wasley, Looney, & Mandic, 2013), but also bringing about an end to musicians' careers (McGinnis & Milling, 2005;Ryan & Andrews, 2009;Yoshie, Kudo, Murakoshi, & Ohtsuki, 2009).…”
Section: Musical Performance Anxietymentioning
confidence: 99%
“…Legtöbbször 15-40% azon zenészek aránya, akik zenei teljesítményszorongással küzdenek (Fishbein, Middlestadt, Ottati, Straus, & Ellis, 1988;Nielsen és mtsai, 2017), de egyes vizsgálatokban ez a szám a 80%-ot is meghaladja (Topoğlu és mtsai, 2018;Zakaria, Musib, & Shariff, 2013). Gyermekekkel végzett vizsgálat alapján 3-4 éves korban kevesebb a koncertet megelőző anticipációs szorongás, ha korábban már játszottak hangversenyen (Boucher & Ryan, 2010); illetve kevesebb szorongásos tünetet tapasztalnak azok, akik hétéves kor előtt kezdik meg zenei tanulmányaikat (Zarza-Alzugaray, Orejudo, Casanova, & Aparicio-Moreno, 2017). Ryan (2004) vizsgálatában a fiúknak több szorongásos tünetük volt fellépés során, azonban a lányok szívritmusa fellépés előtt lényegesen magasabb volt.…”
Section: Prevalenciaunclassified
“…The findings of studies such as those by Kendrick et al (1982) and LeBlanc et al (1997) have established MPA as an issue in this age group but prevalence rates have not been estimated formally (Fehm & Schmidt, 2016). A recent study found that musicians who start their musical training at or before the age of 7 years old tend to report lower anxiety levels in performance than those who commenced after this age (Zarza-Alzugaray et al, 2018).…”
Section: Introductionmentioning
confidence: 99%